Psychosocial risks in accounting personnel - Cantos Lucas, Pablo Antonio; Mite Albán, María Teresa (Revista Universidad de Guayaquil, 2024)
This study aimed to identify the main psychosocial risks (working conditions that can have a negative impact on the health and well-being of the worker), as well as measure the levels of burnout (chronic stress) and resilience (ability to overcome adversities) in personnel. accountant who practices this profession in Guayas-Ecuador, exploring possible relationships between variables. The research is transversal, quantitative and descriptive. There was a sample of 401 people who carry out activities related to accounting, to whom a macro instrument that unified the questionnaires was applied: evaluation of the Ministry of Labor of Ecuador, the MBI General Survey and the CD-RISC reduced resilience scale. The highest (critical) risks identified are: workplace harassment (harassment), double presence (imbalance between work and family), working conditions, self-perceived health, leadership (can be a risk if not exercised adequately by bosses) and recovery (if the subject does not enjoy their rest periods, for example, vacations). In burnout the results were 5% high level, 46% medium and 49% low. That is, 5 out of every 100 of the participating accountants presented burnout and 46 are close to suffering from it. This scenario could worsen, since if the working conditions are less favorable (for example, work overload, insecurity in premises, etc.), the risk of experiencing burnout will be greater. Finally, for resilience the results were: 46.38% high, 40.4% medium and 13.22% low, which implies that the majority of this conglomerate usually has resilient behaviors that would allow them to better cope with stressful situations, observing that people with a higher level of resilience, they perceive themselves as having a better state of physical and mental health, as well as with greater effectiveness in taking on the challenges that the profession demands of them every day, hence the importance of strengthening resilience as a skill.